K‐Functionalized Carbon Quantum Dots‐Induced Interface Assembly of Carbon Nanocages for Ultrastable Potassium Storage Performance. Issue 5 (31st March 2022) - Hu, Yu; Tang, Cheng; Lv, Fengting; Du, Aijun; Wu, Zhong‐Shuai; Zhang, Haijiao
Abstract: Carbon nanocages (CNCs), with unique merits of morphology and structure, have attracted increasing attention for energy storage and conversion. However, the synthesis of CNCs reported so far suffers from relatively harsh conditions and expensive raw materials. Herein, porous CNCs are intelligently designed using low‐cost glucose as the carbon precursor via a facile K‐functionalized carbon quantum dots (K‐CQDs)‐induced assembly route under hydrothermal process. The resulting CNCs have a unique cage‐like structure, large surface area, and rich carboxyl groups. With these elegant structural merits, the as‐made CNCs anode shows a high reversible capacity of 270 mAh g −1 at 100 mA g −1 after 200 cycles and a long‐term cycling stability of 206 mAh g −1 at 2000 mA g −1 after 4000 cycles. An intercalation reaction mechanism with the K + intercalation compound is further identified through an in‐situ Raman technique. Density functional theory simulations reveal that abundant carboxyl groups inherited from K‐CQDs can significantly promote the potassium storage capacities of the CNCs electrode. Abstract : Porous carbon nanocages (CNCs) are developed via a facile K‐functionalized CQDs‐induced hydrothermal assembly route. Thanks to the unique porous cage‐like nanostructure, large specific surface, and rich surface groups, the as‐made CNCs anode shows excellent electrochemical performance for potassium storage, as verified by the theoretical simulation and experimental results.